2016
DOI: 10.1111/ecc.12499
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers reflecting on the early days of childhood cancer

Abstract: Much research examining primary caregivers of children with cancer has focused on their distress levels and coping strategies. Drawing on qualitative data from semi-structured interviews with 38 Australian primary caregivers, this article examines their experiences through their child's cancer diagnosis and early treatment period. However, it does so retrospectively with their child in remission (a minimum of 5 years post diagnosis). This methodology gave caregivers the time to evaluate and reflect on their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 23 publications
3
31
0
6
Order By: Relevance
“…Caregivers in this study reported the complex care for their child became routine and normal for them. These findings are consistent with existing literature in caregivers of children with cancer found that the process of becoming a caregiver (mothers and fathers; n = 38) of a child with cancer included new definitions of normality and approaches to the child's care (Cox, ). Cox () described caregivers gained knowledge and confidence in their child's care and adopted nursing roles by monitoring treatment side effects and examining medical results, which were evident in our findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Caregivers in this study reported the complex care for their child became routine and normal for them. These findings are consistent with existing literature in caregivers of children with cancer found that the process of becoming a caregiver (mothers and fathers; n = 38) of a child with cancer included new definitions of normality and approaches to the child's care (Cox, ). Cox () described caregivers gained knowledge and confidence in their child's care and adopted nursing roles by monitoring treatment side effects and examining medical results, which were evident in our findings.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with existing literature in caregivers of children with cancer found that the process of becoming a caregiver (mothers and fathers; n = 38) of a child with cancer included new definitions of normality and approaches to the child's care (Cox, ). Cox () described caregivers gained knowledge and confidence in their child's care and adopted nursing roles by monitoring treatment side effects and examining medical results, which were evident in our findings. Similarly, caregivers (mothers and fathers; n = 48) of children who had solid organ transplant described care as becoming routine and being confident in their child's care (Lerret, Johnson, & Haglund, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were found in Cox's study (13) , which showed that both parents are impacted by the diagnosis of their children's cancer and both feel like they lost control of the situation and are powerless when faced with the disease, which leads them to seek normality and develop new ways of caring for the child.…”
Section: Discussionsupporting
confidence: 82%
“…Physical, social and emotional overload repercussions are part of the experience of family members who face childhood cancer, especially the father, who deals with his masculine roles in the family and in society (11) . Qualitative studies have been conducted to investigate the experience of the father and other family members with the child or adolescent's cancer diagnosis (9,(12)(13)(14) . Given the above and the importance of further investigate fathers' experience of care, the present study is proposed with the purpose of synthesizing and interpreting results and conclusions of qualitative research addressing the father's experience in the care of the child with cancer.…”
mentioning
confidence: 99%